Discretionary policy and multiple equilibria in a new Keynesian model. (21st November 2019) - Hahn, Volker
Abstract: We show that discretionary policymaking can lead to multiple rational-expectations equilibria where the central bank responds to inflation sentiments, which are driven by past endogenous variables but are unrelated to current economic fundamentals. Some of these equilibria have favourable consequences for welfare, resulting in outcomes superior even to those achieved under timeless-perspective commitment. Inflation sentiments also provide a novel explanation for the sizeable macroeconomic fluctuations in many countries in the 1970s. Compared to interest-rate rules violating the Taylor principle, our explanation has the advantage of providing a rationale for why central banks that are confronted with inefficiently large macroeconomic fluctuations may not be able to deviate to new policies with superior macroeconomic outcomes. Moreover, we show that our approach provides an alternative explanation for the high degree of inflation persistence found in the data.